Exploring Chilean early years educators’ professional identities through their figured worlds - Opazo Perez, Maria Jose (2020)
Chile has a long tradition of early years education, which started 150 years ago. Nowadays, the interest in this educational level has grown, aligned with concerted international evidence which acknowledges the benefits that children have when they attend early years education. However, the evidence regarding early years educators in Chile has been scarce. My research aims to address this by exploring the professional identities of Chilean early years educators, understanding identity as an ongoing and dynamic process. Through the study of their everyday experiences in educational settings funded by the State and based on the qualitative tradition, I adopt a phenomenological approach and visual and narrative methodologies such as photo-elicitation, semi-structured interviews and observations in a purposive sample of nine early years educators. Findings are presented in the form of portraits of each of the participants. By using a practice theory of self and identity, findings show that early years educators are constructing an ethical caring professional identity by developing emotional relationships with children, and by pursuing broader educational purposes, even though they are working in a highly market oriented educational system in Chile. Findings also show that the educators are forming distinctive professional identities, informed by the meetings they have with their colleagues, alongside the training courses they have undertaken. With respect to the implications for Chilean educational policies, I strongly recommend the promotion of such professional collaboration within early years education, since they constitute spaces for authoring, which in turn, strengthens the professional identities of the educators.